2011
DOI: 10.1002/nme.3265
|View full text |Cite
|
Sign up to set email alerts
|

Application of the control volume mixed finite element method to a triangular discretization

Abstract: SUMMARYA two-dimensional control volume mixed finite element method is applied to the elliptic equation. Discretization of the computational domain is based in triangular elements. Shape functions and test functions are formulated on the basis of an equilateral reference triangle with unit edges. A pressure support based on the linear interpolation of elemental edge pressures is used in this formulation. Comparisons are made between results from the standard mixed finite element method and this control volume … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Equations and place somewhat diverse requirements on the test function. In , when test functions of the form ωik~νik/ςik|rFik were used in , it was demonstrated that an optimal weighting resulted. With regard to , two piecewise pressure approximations associated with the test function are investigated herein.…”
Section: Solving the Darcy Problem With Control‐volume Vixed Finite‐ementioning
confidence: 99%
See 4 more Smart Citations
“…Equations and place somewhat diverse requirements on the test function. In , when test functions of the form ωik~νik/ςik|rFik were used in , it was demonstrated that an optimal weighting resulted. With regard to , two piecewise pressure approximations associated with the test function are investigated herein.…”
Section: Solving the Darcy Problem With Control‐volume Vixed Finite‐ementioning
confidence: 99%
“…For the CVMFE method, the vector test function in reference space, truebold-italicω̂i, is obtained from the vector shape function evaluated at the primary face trueF̂i1:truebold-italicω̂i()truebold-italicν̂i1|ζ=0/trueς̂i1 . From , this expression becomes truebold-italicν̂i1|ζ=0trueς̂i1=22Ji[]60.3emnormalΓi3ξnormalΣiηnormalΨi. To obtain an appropriate scaling factor relating truebold-italicω̂i to ()truebold-italicν̂i1|ζ=0/trueς̂i1, property for test functions is used: Qikbold-italicωik·p0.3emdv=trueQ̂1truebold-italicω̂i·truêp0.3emJi0.3emdtruev̂=truep̂itruep̂…”
Section: Solving the Darcy Problem With Control‐volume Vixed Finite‐ementioning
confidence: 99%
See 3 more Smart Citations